Compound-specific radiocarbon dating and mitochondrial DNA analysis of the Pleistocene hominin from Salkhit Mongolia - Thibaut Devièse (Nature Portfolio, 2019)
The Salkhit skull from Mongolia was initially suggested to have archaic hominin characters. Here, Devièse and colleagues date the skull to approximately 34–35 thousand years ago and reconstruct its mitochondrial genome, finding that it falls within modern human haplogroup N found across Eurasia.